THE ENVIRONMENTAL AND SOCIAL IMPACTS OF INDUSTRIALIZATION: LESSON FROM CENTRAL JAVA - Sudharto P. Hadi (JOURNAL OF COASTAL DEVELOPMENT, 1997)
In many developing countries, industrialization is considered as the best way to achieve the economic progress. The general pattern of long-term development of Indonesia’s fifth five year development plan is expected to bring about fundamental changes in the economic structure from agriculture to industrialization. A policy of encouraging industrialization is considered as a means of stimulating the national rate of economic growth, providing employment opportunities and raising the general standard of living of the poor. To support this policy, each municipal government is encouraged to build industrial zones intended to attract and facilities foreign and domestic investors. This research is to identify the environmental and social impacts of industrialization by using two different places of industrial zone as case studies. The impacts studied include environments, socio-economic and socio-cultural. Industrialization as a strategy for economic development has been successful in terms of its contribution to improve Gross Domestic Product (GDP). The industrial sector could create employment opportunities to a particular segment of the population: young, single females. Industrial activities do not create much value added for local people. In fact, local people are adversely affected, threatened by job loss and decrease of daily income. The environment consequences emerged include floods, lack of clean water, water pollution, air pollution, odour, dust, and noise. The indication of social impact is weakening community ties. The household associations in impacted villages are likely to conduct regular meeting as was previously was the habit.